AUTENTICITET OG FIKTIONALITET - I JUNOT DÍAZ’ THE BRIEF WONDROUS LIFE OF OSCAR WAO - Bøndergaard, Johanne Helbo (K&K - Kultur og Klasse, 2013)
AUTHENTICITY AND FICTIONALITY | Traditionally literature on historical traumas such as genocide, war and dictatorship has shown careful respect for the extraordinary and tragic nature of the events in question by representing them in soberly realistic, silent or hermetic forms and in authentic testimonies expressing a general sensitivity to the ethical implications of colourful and enjoyable aesthetics. Recently, though, art and literature on memory and history seems to leave behind testimony and the careful performance of silence exploring instead hybrid forms, interaction with visual media, vibrant language and perspectives other than those of the witness and the victim. Junot Díaz’ novel The Brief Wondrous Life of Oscar Wao (2007) is one example. The hypothesis explored in this article is that Díaz’ loud and colourful book uses fictionality to counter the silence and oppression of death and dictatorship that is also carefully explored. I argue that the excessive use of “genre” references and magical events explores the limits of authentic representation of historical trauma suggesting instead a reading strategy in which history can be approached emotionally and critically through the explicit use of fictionality.